The Past, The Present, and The Future - Souleles, Nicos (My University, 2026)
Icons and symbols are used to convey messages belonging to the three times. Metaphors and Metonymies to engage… Is web publishing multimedia, or desktop publishing? Can we deliver an experience? The Past, the Present & The Future is a possible template of what can be done… (ISEA97: Eighth International Symposium on Electronic Art)